Development of spin card question media based on the canva website that is suitable for use in Pancasila education learning - Kurniawati, Vanny Dwi; Suhartono, H. Edi; Rochmadi, Nur Wahyu (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2026)
Website-based spin card question media displays smart cards and quiz cards. Smart cards contain barcodes connected to the website, quiz cards contain questions related to learning materials. Development of learning media as a solution to the problem of low intrinsic motivation of students towards the material. Research on the development of website-based spin card question media was developed using the Borg & Gall research model with 9 stages. This research on the development of website-based Spin Card Question media at SMPN 1 Sambeng is very suitable for use in learning activities, especially in Pancasila Education subjects. The results of the feasibility assessment from material experts got a score of 75, media experts got a score of 92, language experts got a score of 90, users (teachers) got a score of 90 with, and trials on 30 students showed a significant increase in learning outcomes. The average pretest result was 63.20 to posttest 84.23 and p-value